Analisa Sistem Pakar Metode Bayes Dalam Mendiagnosa Penyakit Tubercolosis - Muhammad Ridho Syahwana; R. Mahdalena Simanjorang (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2022)
Tubercolosis is an infection caused by acid-resistant bacilli (AFB). Tubercolosis is an infectious disease that can attack anyone through the air. Tuberculosis is a dangerous infectious disease. Tuberculosis is a chronic or chronic disease that can strike between the ages of 15-35 years. How to diagnose Tuberculosis is by expert experts interviewing and then testing sputum samples by using a laboratory to find out positive or negative Tuberculosis so it requires a long time. Therefore we need an Expert System with Bayes method to facilitate diagnosing tuberculosis disease. This expert system was developed using the Microsoft Visual Studio 2010 programming language and by using a Microsoft Access 2010 database.